PENGARUH PROFITABILITAS DAN KEPEMILIKAN MANAJERIAL TERHADAP RETURN SAHAM PERUSAHAAN SUBSEKTOR FOOD AND BEVERAGE DI INDONESIA: SEBELUM DAN MASA PANDEMI COVID-19 - Gernadi, Rikeliani; Sparta (Journal of Accounting, Management and Islamic Economics, 2025)
This study aims to determine the effect of Earning Per Share and Managerial Ownership on Stock Returns with the Covid-19 Pandemic as moderating variables for independent variables.The research sample consisted of 18 food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2016-2020. The data analysis technique used was descriptive statistics, classical assumption test and multiple linear regression analysis. The results of the study state that Earning Per Share has a positive effect on Stock Return, Managerial Ownership has a positive effect on Stock Return, the Covid-19 Pandemic does not affect Earning Per Share on Stock Return, the Covid-19 Pandemic does not affect Managerial Ownership on Stock Return. The results of the study have implications for the company to increase the value of Earning Per Share by preparing strategies and increasing managerial ownership where this will encourage investor confidence to invest in the company.